Water Quality Characteristics of a Water Hyacinth Infested Tropical Highland Lake: Lake Tana, Ethiopia - Dersseh, Minychl G.; Steenhuis, Tammo S.; Kibret, Aron A.; Eneyew, Bantesew M.; Kebedew, Mebrahtom G.; Zimale, Fasikaw A.; Worqlul, Abeyou W.; Moges, Mamaru A.; Abebe, Wubneh B.; Mhiret, Demesew A.; Melesse, Assefa M.; Tilahun, Seifu A. (Frontiers in Water, 2022)
Nutrient enrichment from increased anthropogenic activities causes algal blooms and the proliferation of water hyacinth and other aquatic weeds. It is a recent phenomenon in developing nations where the link between water quality and water hyacinth infestation is not well studied. The objective of this study is to investigate the relationship between phosphorus, nitrogen, and chlorophyll-a on the distribution of water hyacinths in Lake Tana, located in the tropical highlands of Ethiopia. In this 3,000 km2 lake, water hyacinths have expanded from almost none to 25 km2 during the last 10 years. Water samples were taken near the four large rivers and at 27 nearshore stations. Samples were analyzed for total phosphorus, total nitrogen and chlorophyll-a. Our measurements were augmented with concentrations reported in the literature historically. Our results show that phosphorus concentration increased exponentially since the first measurements in 2003 from 0.01 mg P/l to near 1.8 mg P/l in 2020. Nitrogen concentrations increased from near zero at the end of the dry phase but remained nearly constant at around 2 mg total N/l after 2016. As a result, the ratio of nitrogen and phosphorus decreased in time, and the lake went from phosphorus to nitrogen limiting. Chlorophyll-a concentrations ranged from 0.3 to 104 μg/l. Water hyacinths appeared in the lake around 2010 after the nitrogen assimilation capacity of the lake was exceeded. They are found mainly in the northeastern part of Lake Tana, while nutrient concentrations are suitable for growing water hyacinths throughout the lake after 2010. Its location is mainly a consequence of lake circulation and wind direction. Minimum Chl-a concentrations were measured at locations with water hyacinths. Preventing future expansion of water hyacinth in Lake Tana is complicated but will require at minimum management practices that reduce the nitrogen and phosphorus loading from fertilizers applied in agriculture and prevent contributions from point sources.